A novel electrochemical device as a disinfection system to maintain water quality during washing of ready to eat fresh produce. (January 2017) - Gómez-López, Vicente M.; Gil, Maria I.; Allende, Ana
Abstract: Electrolyzed water (EW) is known by its bactericidal efficacy and capability to oxidize organic matter. The present research evaluated the efficacy of recently developed electrolytic cells able to generate higher concentration of reactive oxygen species using lower power and salt concentration than conventional cells. This study tested the inactivation of Escherichia coli O157:H7, the organic matter depletion and trihalomethane (THM) generation by EW in process wash water under dynamic conditions. To achieve this, clean tap water was continuously added up to 60 min with artificial process water with high chemical oxygen demand (COD) inoculated with E. coli O157:H7, in experiments performed in a pilot plant that recirculated water through one electrolytic cell. Plate counts of E. coli O157:H7, COD, THMs, free, combined and total chlorine, pH, temperature and oxidation-reduction potential were determined. Results indicate that the novel electrolysis system combined with minimal addition of NaCl (0.05%) was able to suppress E. coli O157:H7 population build-up and decreased the COD accumulation in the process wash water. THM levels in the water were relatively high but its concentration in the washed product was marginal. Highly effective electrolysis has been proven to reduce the occurrence of foodborne diseases associated to cross-contamination in produce washers without having an accumulation of THMs in the washed product. Highlights: Cross-contamination of fresh produce during washing represents a risk. A highly efficient electrochemical device inhibited cross-contamination. The electrochemical treatment also reduced the accumulation of organic matter. High concentrations of trihalomethanes (THM) were accumulated in the water. THM levels in baby spinach washed in this water were marginal.